Electrophysiology of gliomas: current science, implications, and opportunities - Minns, Hanna E.; Useinovic, Nemanja; Smith, Jordan L.; Puri, Sushant; Raslan, Ahmed M.; Paulk, Angelique C.; Cleary, Daniel R. (Frontiers in Oncology, 2026)
Gliomas engage in bidirectional communication with neurons, promoting hyperexcitable conditions that enable neural circuit infiltration and drive tumor growth. These neuron-glioma interactions create patterns of aberrant neural activity that can be detected using intracranial electrodes. While conventional clinical electrodes are limited by low spatiotemporal resolution and lack of single-unit precision, recent advances in neural engineering have introduced multiple types of high-density electrodes that provide orders of magnitude greater spatial resolution. Pairing these tools with emerging characterizations of novel, glioma-associated electrophysiological signatures offers new opportunities to understand disease progression and improve surgical and medical management for gliomas and glioma-related epilepsy. In this review, we begin by outlining foundational research in cancer neuroscience and neuron-glioma interactions through the lens of extracellular dynamics. We then discuss established and emerging methods for intraoperative evaluation of neural activity, what is known about glioma-associated oscillatory and aperiodic trends, and implications for future studies. Finally, we consider the therapeutic potential of neuromodulation for gliomas.